THE ENEOLITHIC OF KAZAKHSTAN: THE HISTORY OF STUDY AND THE MAIN PROBLEMS - Slavchev, V.; Baigunakov, D.; Sabdenova, G. (Journal of history, 2018)
The article deals with the problems of the Eneolithic of Kazakhstan. The history of the study is systematized. The main problems are considered. Eneolithic monuments are well researched in the northern regions of Kazakhstan.The Botay culture is especially prominent, which was named after the village name.It was singled out by archaeologist V.F. Zaibert. About 20 settlements along the steppe rivers are opened. The reference monument is the Botay settlement. Archaeologists have calculated that more than 250 houses were built here by ancient people.The area of semi-dwelling houses was 20-70 square meters. As a result of many years of excavation, numerous tools of labor were discovered.A large number of bone remains were found in the Botay settlement.In addition to the bones of wild animals, everywhere there are a lot of bones belonging to the horse.This proves the signs of domestication. The study of several local groups (Tersek group, Shidertin group) of monuments by other scientists (V. Logvin, V. Mertz) allowed to expand the geography of the Botay Eneolithic culture, to give its versatile description, to clarify the main problems of the Eneolithic of Kazakhstan. Many regions of Kazakhstan, especially the Central, Eastern, Southern parts have not yet comprehensively understood. According to some findings, only some areas known to have a few Eneolithic monuments.In the future, researchers should work in this area to find out the historical and cultural processes in the Eneolithic.